Molecular characteristics and antimicrobial resistance of invasive pneumococcal isolates from children in the post-13-valent pneumococcal conjugate vaccine era in Shenzhen, China - Lu Huang; Yanmin Bao; Qiuwei Yi; Dingle Yu; Heping Wang; Hongmei Wang; Zihao Liu; Chunqing Zhu; Qing Meng; Yunsheng Chen; Wenjian Wang; Jikui Deng; et al. (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Objectives: This study aimed to evaluate the molecular epidemiology and antimicrobial resistance of invasive pneumococcal isolates from children in Shenzhen, China, in the early stage of the pneumococcal 13-valent conjugated vaccine (PCV-13) era from 2018 to 2020. Methods: Invasive pneumococcal strains were isolated from hospitalized children with invasive pneumococcal diseases (IPDs) from January 2018 to December 2020. The serotype identification, multilocus sequence typing (MLST), and antibiotic susceptibility tests were performed on all culture-confirmed strains. Results: Sixty-four invasive strains were isolated mainly from blood (70.3%). Prevalent serotypes were 23F (28.1%), 14 (18.8%), 19F (15.6%), 6A/B (14.1%), and 19A (12.5%), with a serotype coverage rate of 96.9% for PCV13. The most common sequence types (STs) were ST876 (17.1%), ST271 (10.9%), and ST320 (7.8%). Half of the strains were grouped in clonal complexes (CCs): CC271 (21.9%), CC876 (20.3%), and CC90 (14.1%). Meningitis isolates showed a higher resistance rate (90.9% and 45.5%) to penicillin and ceftriaxone than the rate (3.8% and 9.4%) of non-meningitis isolates. The resistance rates for penicillin (oral), cefuroxime, and erythromycin were 53.13%, 73.4%, and 96.9%, respectively. The dual ermB and mefA genotype was found in 81.3% of erythromycin-resistant strains. The elevated minimum inhibitory concentration (MIC) of β-lactam antibiotics and dual-genotype macrolide resistance were related mainly to three major serotype-CC combinations: 19F-CC271, 19A-CC271, and 14-CC876. Conclusion: Invasive pneumococcus with elevated MICs of β-lactams and increased dual ermB and mefA genotype macrolide resistance were alarming. Expanded PCV13 vaccination is expected to reduce the burden of paediatric IPD and to combat antibiotic-resistant pneumococcus in Shenzhen.